Transcriptional Analysis of Lennert Lymphoma Reveals a Unique Profile and Identifies Novel Therapeutic Targets - Etebari, Maryam; Navari, Mohsen; Agostinelli, Claudio; Visani, Axel; Peron, Cristiano; Iqbal, Javeed; Inghirami, Giorgio; Piccaluga, Pier Paolo (Frontiers in Genetics, 2019)
Lennert lymphoma (LL) is a lymphoepithelioid morphological variant of peripheral T-cell lymphoma/not otherwise specified (PTCL/NOS), clinically characterized by better prognosis if compared to other PTCL/NOS. Although well characterized as far as morphology and phenotype are concerned, very little is known regarding its molecular features. In this study we investigated the transcriptional profile of this tumor aiming 1) to identify its cellular counterparts; 2) to better define its relation with other PTCLs – and therefore its possible position in lymphoma classification; and 3) to define pathogenetic mechanisms, possibly unveiling novel therapeutic targets. To address these issues we performed gene and microRNA expression profiling on LL and other PTCL/NOS cases; we identified different genes and microRNAs that discriminated LL from other PTCL/NOS. Particularly, LL revealed a molecular signature significantly enriched in helper function and clearly distinguishable from other PTCL/NOS. Furthermore, PI3K/Akt/mTOR pathway emerged as novel potential therapeutic target. In conclusion, based on the already known particular morphological and clinical features, the new molecular findings support the hypothesis that LL might be classified as a separate entity. Pre-clinical and clinical studies testing the efficacy of PI3K/MTOR inhibitors in this setting are warranted.